2002
DOI: 10.1097/00129334-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Forefoot Ulcer Healing Using Alternative Off-loading Methods in Patients with Diabetes Mellitus

Abstract: The healing rate of forefoot ulcerations in patients with diabetes using alternative off-loading methods or a total contact cast appeared to be comparable when the method was selected based on location of ulcer, patient age, and duration of ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 24 publications
2
76
0
2
Order By: Relevance
“…The other evidence largely describes clinical outcomes from predominantly prospective and retrospective epidemiological studies of various offloading techniques [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Between 73% and 100% of wounds were reported to have healed in studies of TCCs, with healing times ranging between 30 and 63 days [23,29,39]. Fiberglass cast shoes were found to heal 91% of subjects in an average of 34 days [32].…”
Section: Ulcer Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The other evidence largely describes clinical outcomes from predominantly prospective and retrospective epidemiological studies of various offloading techniques [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Between 73% and 100% of wounds were reported to have healed in studies of TCCs, with healing times ranging between 30 and 63 days [23,29,39]. Fiberglass cast shoes were found to heal 91% of subjects in an average of 34 days [32].…”
Section: Ulcer Treatmentmentioning
confidence: 99%
“…Fiberglass cast shoes were found to heal 91% of subjects in an average of 34 days [32]. Studies of Scotch-cast boots, windowed casts, and custom splints have reported between 70% and 81% of subjects healed between 42 and 300 days [23,40,41].…”
Section: Ulcer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also reports of good healing outcomes achieved with devices such as felt deflection and healing shoes. 109,110,115 Emerging reports support surgical offloading to prevent recurrence where foot deformity is the cause of ulceration, and other treatments to heal or prevent recurrence have failed. 116,117 This is reflected in the latest international guidelines from the IWGDF, which recommend surgical procedures to achieve pressure offloading.…”
Section: Neuropathy Deformity and Offloadingmentioning
confidence: 99%